2019
DOI: 10.1038/s41598-019-48418-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of initiating continuous renal replacement therapy in septic shock patients with acute kidney injury

Abstract: Acute kidney injury (AKI) in patients with septic shock is associated with high mortality, but the appropriate timing for initiating continuous renal replacement therapy (CRRT) is controversial. We retrospectively enrolled 158 septic shock patients with AKI in the medical intensive care unit (ICU) from July 2016 to April 2018. The time from AKI onset to CRRT initiation was compared according to ICU mortality using Cox proportional hazard, receiver operating characteristic, and Kaplan-Meier survival analyses. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 28 publications
4
28
0
1
Order By: Relevance
“…4). In cohort studies [25][26][27][28][29][30][31] there was a statistically significant decrease in mortality among patients who received early RRT (OR 0.42; 95% CI 0.30 to 0.40; I 2 21%), while mortality in the RCTs [20,24](OR 1.1; 95% CI 0.84 to 1.45; I 2 0%) was not statistically significant.…”
Section: Primary Outcomesmentioning
confidence: 93%
See 4 more Smart Citations
“…4). In cohort studies [25][26][27][28][29][30][31] there was a statistically significant decrease in mortality among patients who received early RRT (OR 0.42; 95% CI 0.30 to 0.40; I 2 21%), while mortality in the RCTs [20,24](OR 1.1; 95% CI 0.84 to 1.45; I 2 0%) was not statistically significant.…”
Section: Primary Outcomesmentioning
confidence: 93%
“…Nine studies [20,[24][25][26][27][28][29][30][31] with a total of 1694 patients ultimately met our criteria (Table 1). These references included two RCTs [20,24] and seven retrospective cohort studies [25][26][27][28][29][30][31]. The characteristics and methodological quality of all trials in the meta-analysis are shown in Table 1 and the outcomes in septic patients with AKI are shown in Table 2.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations